2016
DOI: 10.1111/jora.12260
|View full text |Cite
|
Sign up to set email alerts
|

The Shared Etiology of Attentional Control and Anxiety: An Adolescent Twin Study

Abstract: We investigated the etiology of attentional control (AC) and four different anxiety symptom types (generalized, obsessive-compulsive, separation, and social) in an adolescent sample of over 400 twin pairs. Genetic factors contributed to 55% of the variance in AC and between 43 and 58% of the variance in anxiety. Negative phenotypic associations between AC and anxiety indicated that lower attentional ability is related to increased risk for all 4 anxiety categories. Genetic correlations between AC and anxiety p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 104 publications
1
8
0
Order By: Relevance
“…The primary contribution of this work is evidence that the same genetic and nonshared environmental factors are associated with the presence of attentional control deficits, ADHD symptoms, and symptoms of GAD and social phobia. This finding corroborates research linking genetic influences on attentional control with anxiety symptoms (Gagne et al., ) and advances attentional control as a putative mechanism in the comorbidity of ADHD and anxiety during the adolescent years, when both types of problems are salient. Our findings also supplement those from other approaches, such as GWAS, which have found relatively little overlap in polygenic risk scores for children's behavioral problems from early/middle childhood to late childhood/adolescence (Meier et al., ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The primary contribution of this work is evidence that the same genetic and nonshared environmental factors are associated with the presence of attentional control deficits, ADHD symptoms, and symptoms of GAD and social phobia. This finding corroborates research linking genetic influences on attentional control with anxiety symptoms (Gagne et al., ) and advances attentional control as a putative mechanism in the comorbidity of ADHD and anxiety during the adolescent years, when both types of problems are salient. Our findings also supplement those from other approaches, such as GWAS, which have found relatively little overlap in polygenic risk scores for children's behavioral problems from early/middle childhood to late childhood/adolescence (Meier et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…In a sample that partially overlapped with this study's sample, additive genetic variance accounted for covariation between slightly different aspects of parent‐ and experimenter‐rated attentional control and parent reports of internalizing or externalizing symptoms in early to middle childhood (Lemery‐Chalfant et al., ). Previous work also suggested that generalized and social anxiety symptoms shared 17% to 18% of their variance, respectively, with attentional control during adolescence (Gagne, O'Sullivan, Schmidt, Spann, & Goldsmith, ). In both of these reports, genetic correlations between attentional control and internalizing problems were negative, suggesting that similar genetic factors may contribute to both impairments in attentional control and anxiety symptoms.…”
mentioning
confidence: 89%
“…There is a substantial genetic overlap concerning AC ability and trait anxiety (Gagne et al, 2017). For example, Attentional Control Theory (Eysenck, Derakshan, Santos, & Calvo, 2007) suggests that AC impairments in elevated trait anxiety predict increased cognitive interference, which is further exacerbated if the distracting stimuli are threat-related.…”
mentioning
confidence: 99%
“…Shared genetic factors also accounted for co-occurring anxiety and ADHD symptoms, even after controlling for attention. Also, shared genetic factors explained the association between adolescent attentional control and four subtypes of anxiety (e.g., general anxiety, separation anxiety, social anxiety and obsessive-compulsive anxiety), with some specificity and distinct etiology for anxiety subtypes (Gagne et al, 2017).…”
Section: Comorbidity Of Attention Measures With Adhd and Anxietymentioning
confidence: 99%